Diffusion processes in the transition layer of the Earth's magnetosphere - Prokhorenkov, A.S.; Kozak, L.V.; Lui, A.T.Y.; Gala, I.V. (Advances in Astronomy and Space Physics, 2015)
Turbulence has a different nature in the interplanetary magnetic field and in the transition region, thus it requires a different type of analysis. The "Cluster 2" satellite mission provides magnetic measurements with a temporal resolution of 22.5 Hz. We analysed the evolution of the probability density function over time, as well as that of the structural function. From the analysis we can conclude that for small time scales, the fluctuation distribution differs significantly from the Gaussian. Furthermore, we see that in the foresho k region, the fluctuation be comes almost Gaussian. Using the extended self-similarity structure function we compare the experimental data with the Kolmogorov K41 model. Calculated diffusion coeficients have a good agreement with the analysis of the probability density function and this can prove the existence of superdiffusion processes in the transition region of the Earth's magnetosphere.